Basic Reproduction Number of Infectious Disease in Heterogeneous Environment: A Scoping Review (CSIAM Transactions on Life Sciences, 2025)
This paper overviews the recent advances how spatial-temporal heterogeneity affects the spread of epidemic diseases from the perspective of basic reproductionnumber. First part focuses upon the theoretical studies and applications of seasonaleffects on infectious invasion. Then the investigations are introduced to demonstratethe role of spatial structure and spatial contact patterns in the prevention of diseaseoutbreaks. Suggestions are presented for potential future researches.
Keywords: Epidemic; threshold; fluctuation; diffusion; stability.